Gebeliğin ilk trimestırında iohexol maruziyeti, vaka sunumu - KAŞKAL, MERT; GÖREN, MEHMET ZAFER (My University, 2023)
We report a case of a 38-year old pregnant exposed to iohexol who admitted to our teratology information service (TIS). The data was collected by face to face interview and a written consent was taken. She reported that she was given metoprolol for her chest pain and palpitations and she had underwent a cardiac CT investigation with contrast agent iohexol. The patient became aware of her pregnancy in the 6th week after her last menstrual period and admitted to our TIS for the safety of her pregnancy. Metoprolol was used during the 5th and 6th weeks. Radiology consultation was also asked for checking the safety of the dose of radiation she was exposed. During the follow up, she reported that her pregnancy ended as a miscarriage in the 10th week.
Keywords: Eczacılık; Sağlık Bilimleri; Pharmacology and Therapeutics; Health Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; Clinical Medicine (MED); Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Yaşam Bilimleri; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Life Sciences